A rapid clinic-based service for an emergency department of a tertiary teaching hospital during a dengue outbreak. Issue 14 (9th April 2021) - Shih, Hsin-I.; Huang, Yi-Ting; Hsieh, Chih-Chia; Sung, Tzu-Ching
Abstract : Abstract: The 2015 dengue outbreak in southern Taiwan turned into a public health emergency, resulting in a large-scale mobilization of personnel from the emergency department (ED) services operating in and near full capacity to assist with the outbreak. This study aimed to assess a rapid independent clinic-based service (RCS), which was set up and designed to relieve the overcrowding of the regular ambulatory and emergency services during an epidemic of dengue. This is a retrospective cross-sectional study. National Cheng Kung University Hospital, Tainan, Taiwan. Patients with positive test results were enrolled and reviewed to evaluate the efficacy of RCS implementation between August and October 2015. The case-treatment rates stratified by length of stay (LOS) were used to examine the performance of the RCS that was set up outside the ED and designed to relieve the overcrowding of the regular ambulatory and emergency services. Patients with dengue-like illnesses may arrive at the hospital and require optimal ED triage and management thereafter. Although the outbreak resulted in a shortage of spare space in the ED, a proper response from the hospital administration would ameliorate the work overload of the staff and would not decrease the quality of care for critical patients. An early and restrictive intensive intervention was beneficial to health care facilities during a dengue outbreak. Further planning and training of the RCS could be crucial for hospital preparedness for infectious disease outbreaks.